A synopsis on the Chinese species of Clytra Laicharting, with description of two new species (Coleoptera: Chrysomelidae: Cryptocephalinae: Clytrini) - Wang, Feng-Yan; Zhou, Hong-Zhang (Zootaxa, 2011)
The taxonomy of the genus Clytra Laicharting, 1781 occurring in China is studied. Two new species are described: Clytra (Clytraria) tanae sp. nov. from Qinghai and Yunnan, and Clytra (Clytraria) truncatula sp. nov. from Xinjiang. The Chinese fauna of the genus is thus increased to 13 species/subspecies in total. Keys to the Chinese genera of Clytrini and to Chinese species of Clytra are provided in addition to color plates and line drawings of habitus, maxilla, labium, male genitalia and spermatheca, which facilitates species identification; geographic distributions of 12 species/subspecies are mapped. The type specimens are deposited in Institute of Zoology, Chinese Academy of Sciences, Beijing, China.